Does autoimmune diseases increase the risk of frailty? A Mendelian randomization study - Zhou, Jinlei; Zhang, Yuan; Ni, Ting; Li, Yanlei; Shao, Haiyu; Wang, Fei; Xu, Sen; Huang, Yazeng; Zhang, Jun; Zhao, Tingxiao (Frontiers in Endocrinology, 2024)
Background The causality of autoimmune diseases with frailty has not been firmly established. We conducted this Mendelian randomization (MR) study to unveil the causal associations between autoimmune diseases with frailty. Methods A MR analyses were performed to explore the relationships between autoimmune disease and frailty, using summary genome-wide association statistics. Results Through a comprehensive and meticulous screening process, we incorporated 46, 7, 12, 20, 5, and 53 single nucleotide polymorphisms (SNPs) as instrumental variables (IVs) for hypothyroidism, hyperthyroidism, rheumatoid arthritis (RA), type 1 diabetes (T1D), multiple sclerosis (MS), and overall autoimmune disease, respectively. Our analysis revealed that hypothyroidism (OR = 1.023, 95% CI: 1.008–1.038, p = 0.0015), hyperthyroidism (OR = 1.024, 95% CI: 1.004–1.045, p = 0.0163), RA (OR = 1.031, 95% CI: 1.011–1.052, p = 0.0017), T1D (OR = 1.011, 95% CI: 1.004–1.017, p = 0.0012), and overall autoimmune disease (OR = 1.044, 95% CI: 1.028–1.061, p = 5.32*10^-8) exhibited a positive causal effect on frailty. Conversely, there may be a negative causal association between MS (OR = 0.984, 95% CI: 0.977–0.992, p = 4.87*10^-5) and frailty. Cochran’s Q test indicated heterogeneity among IVs derived from hypothyroidism, hyperthyroidism, T1D, and overall autoimmune diseases. The MR-Egger regression analyzes revealed an absence of horizontal pleiotropy in any of the conducted analyses. Conclusion This study elucidates that hypothyroidism, hyperthyroidism, RA, T1D, and overall autoimmune disease were linked to an elevated risk of frailty. Conversely, MS appears to be associated with a potential decrease in the risk of frailty.